Public Lands and Land Institutions in the State of Rio de Janeiro (1890–2020): a tale of gaps - Ferreira, Álvaro Mendes (Cadernos do Desenvolvimento Fluminense, 2026)
This paper discusses the institutions in the state of Rio de Janeiro that have been involved in finding public lands since the end of the 19th century. There have been great administrative gaps between the institutions, which prevented the emergence of a competent professional field. We conclude that, less than just bureaucratic inefficiency, as neo-institutionalist authors would surmise, Rio de Janeiro’s land institutions were much more hampered by a structural contradiction: territorial control by the state and unchecked land grabbing by the big landowners. The ultimate aim of the discussion is to build a comprehensive socio-historical model of land dynamics in Rio de Janeiro in the 20th and 21st centuries.